“FORMULATION, CHARACTERIZATION AND IN VITRO EVALUATION OF BETULINIC ACID-LOADED LIPID NANOCARRIERS FOR ENHANCED BIOAVAILABILITY AND SUSTAINED RELEASE IN LUNG CANCER THERAPY” (Cuestiones de Fisioterapia, 2025)
Betulinic Acid, a bioactive compound with significant anticancer potential, suffers from poor solubility and low bioavailability, limiting its therapeutic efficacy. This study aimed to develop Betulinic Acid loaded lipid nanocarriers (BALNCs) to enhance drug solubility, bioaccessibility, and controlled release. With particle diameters between 42 and 44 nm, a polydispersity index (PDI) of approximately 0.26, and a zeta potential of approximately 20 mV, the nanocarriers were effectively synthesised and characterised, guaranteeing stability. High encapsulation efficiency (82–86%) and controlled loading capacity were achieved, demonstrating effective drug entrapment.